(untitled) (Research, Society and Development, 2025)
Objective: To identify in the scientific literature how partner participation has been during antenatal care. Method: An integrative literature review that followed PRISMA recommendations and was guided by the PICO strategy. Article searches were conducted in the databases: LILACS, BDENF, and PUBMED, using the cross-referencing of descriptors: “antenatal care”, “paternity”, “father”, in Portuguese, English, and Spanish. Results: Fourteen studies published between 2014 and 2024 were included in this review. The data was analyzed according to four thematic categories: 1) Partners’ perceptions of their involvement in prenatal care, 2) Barriers to partner involvement in prenatal care, 3) Pregnant women’s perceptions of partner involvement in prenatal care, and 4) Nurses’ roles in prenatal care. Conclusion: Scientific evidence demonstrates that the partner’s participation in prenatal care is fundamental for the well-being of the pregnant woman and the baby, strengthening the family bond, and providing emotional support. Unfortunately, paternal presence at consultations is still insufficient, evidencing a significant absence.